Diurnal heating and cooling of a sloping water body with vegetated shallow regions - Prinos, Panagiotis; Papaioannou, Vassilios (Environmental fluid mechanics (Dordrecht, Netherlands : 2001), 2024)
In this work, diurnal heating, by solar radiation, and cooling in a sloping water body with vegetated shallow regions are investigated numerically. The sloping water body consists of a vegetated region with a bottom slope equal to 0.1 and a deep region with a horizontal bottom. The Volume-Averaged Navier-Stokes equations together with the Volume-Averaged Energy equation are solved numerically in the vegetated region. The latter has porosity equal to 0.85 (typical of aquatic plants found in lakes) and a length equal to the total length of the sloping region. At the top free surface, a time-dependent thermal forcing is applied, which is reduced in the vegetated region. Shallow water is considered with a maximum water depth being less than the penetration depth of the solar radiation. The non-vegetated sloping water body is also considered for validation purposes. The results (isotherms, streamlines, exchange flow rate), after ten full thermal forcing cycles, indicate significant vegetation effects on the daytime and night circulation and the exchange flow rates.